2017
DOI: 10.1371/journal.pone.0175473
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Culex quinquefasciatus larvae responses to Lysinibacillus sphaericus Bin toxin

Abstract: Lysinibacillus sphaericus produces the mosquito larvicidal binary toxin consisting of BinA and BinB, which are both required for toxicity against Culex and Anopheles larvae. The molecular mechanisms behind Bin toxin-induced damage remain unexplored. We used whole-genome microarray-based transcriptome analysis to better understand how Culex larvae respond to Bin toxin treatment at the molecular level. Our analyses of Culex quinquefasciatus larvae transcriptome changes at 6, 12, and 18 h after Bin toxin treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The intrinsic apoptotic pathway is specifically activated in response to mitochondria damage, resulting in the cytochrome C release from these organelles and caspases activation that leads to other events, including DNA degradation [72]. A higher expression of caspase 3 in susceptible larvae treated with Bin toxin was an effect caused by this toxin to the cells [73]. The action of Bin toxin induces autophagy in the midgut cells and subsequent cytoplasmic vacuolization as it has been well documented in larvae subjected to Bin treatment [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic apoptotic pathway is specifically activated in response to mitochondria damage, resulting in the cytochrome C release from these organelles and caspases activation that leads to other events, including DNA degradation [72]. A higher expression of caspase 3 in susceptible larvae treated with Bin toxin was an effect caused by this toxin to the cells [73]. The action of Bin toxin induces autophagy in the midgut cells and subsequent cytoplasmic vacuolization as it has been well documented in larvae subjected to Bin treatment [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptome analysis comparing untreated and Bin-treated Cx. p. quinquefasciatus larvae revealed differential expression of transcripts involved in mitochondria mediated apoptosis and autophagy responses [ 174 ]. Another study comparing susceptible and Bin-resistant larvae revealed an outstanding differential expression of transcripts involved in apoptosis and DNA metabolism [ 175 ].…”
Section: Toxins and Mode Of Actionmentioning
confidence: 99%
“…An association between toxicity to insects with growth has been reported, for instance, for spinosad, a biological larvicide based on metabolites of the bacterium Saccharopolyspora spinosa that acts as a neurotoxin [44] which has been recently investigated for its potential effects as an insect growth regulator [45,46]. DEGs possibly related to the toxin mode of action could also be those encoding for regulators of DNA damage, as evidence for the involvement of apoptosis in the mode of action of Bin and Cry toxins has been shown [47][48][49]. Indeed, the transcriptome of the RIAB59 resistant larvae also pointed out several DEGs related to apoptosis and DNA maintenance [26].…”
Section: Discussionmentioning
confidence: 99%